Family and Community Participation in the Development of Early Childhood Education after the Policy Program of one Village one ECE - Waluyo, Edi; Dewanti Handayani, Sri Sularti; Diana, Diana (Universitas Negeri Semarang, 2018)
Family and community participation in Early Childhood Education (ECE) after the policy program of one village one ECE shows that overall they can implement the program thoroughly, there is a need for close and more organized links between the village governments, ECE institutions and communities so that solutions and policies for internal problems in the ECE can be found together. Strengthening services with one village one ECE is a necessity in the hope that children in rural areas will be educated early on. Applying one village at least one ECE requires a lot of participation from various parties including the government at the village level.